Non-profit drug research and development: the case study of Genethon - Szymon Jarosławski; Mondher Toumi (Taylor & Francis Group, 2019)
Non-profit drug research and development (R&D) has the potential to deliver innovative treatments at affordable prices. Using the case study methodology, we discuss some ethical and economic issues, including the possible impact of non-profit companies on innovation efforts from for-profit firms. Like other non-profits, Genethon is willing to adopt an ethical attitude toward their donors by pricing their products affordably. It remains to be seen if the approach to internalize the marketing authorization, manufacturing and distribution activities prove to be efficient and sustainable. Also, the firm faces an ethical dilemma because lower prices of innovative drugs can dry the for-profit R&D in the area and prevent patient access to future innovations.